Endophytic fungi harbored in the root of Sophora tonkinensis Gapnep: Diversity and biocontrol potential against phytopathogens. Issue 3 (15th March 2017) - Yao, Yu Qun; Lan, Fang; Qiao, Yun Ming; Wei, Ji Guang; Huang, Rong Shao; Li, Liang Bo
Abstract: This work, for the first time, investigated the diversity of endophytic fungi harbored in the xylem and phloem of the root of Sophora tonkinensis Gapnep from three geographic localities with emphasis on the influence of the tissue type and geographic locality on endophytic fungal communities and their potential as biocontrol agents against phytopathogens of Panax notoginseng . A total of 655 fungal strains representing 47 taxa were isolated. Forty‐two taxa (89.4%) were identified but not five taxa (10.6%) according to morphology and molecular phylogenetics. Out of identifiable taxa, the majority of endophyte taxa were Ascomycota (76.6%), followed by Basidiomycota (8.5%) and Zygomycota (4.3%). The alpha‐diversity indices indicated that the species diversity of endophytic fungal community harbored in the root of S. tonkinensis was very high. The colonization and species diversity of endophytic fungal communities were significantly influenced by the geographic locality but not tissue type. The geographic locality and tissue type had great effects on the species composition of endophytic fungal communities. Forty‐seven respective strains were challenged by three fungal phytopathogens of P. notoginseng and six strains exhibited significant inhibitory activity. It was noteworthy that endophytic Rhexocercosporidium sp. and F. solani strongly inhibited pathogenic F. solani and other fungal phytopathogens of P. notoginseng . Abstract : The diversity of endophytic fungi harbored in the root of S. tonkinensis was high. The tissue type and geographic locality influenced endophytic fungal communities. Six strains exhibited significant inhibitory activity against three fungal phytopathogens of P. notoginseng .